Biosynthesis of gold and silver nanoparticles using emblica officinalis fruit extract, their phase transfer and transmetallation in an organic solution - Ankamwar, Balaprasad; Damle, C.; Ahmad, Absar; Sastry, M. (Journal of Nanoscience and Nanotechnology, 2005)
The design, synthesis and characterization of biologically synthesized nanomaterials have become an area of significant interest. In this paper, we report the extracellular synthesis of gold and silver nanoparticles using Emblica Officinalis (amla, Indian Gooseberry) fruit extract as the reducing agent to synthesize Ag and Au nanoparticles, their subsequent phase transfer to an organic solution and the transmetallation reaction of hydrophobized silver nanoparticles with hydrophobized chloroaurate ions. On treating aqueous silver sulfate and chloroauric acid solutions with Emblica Officinalis fruit extract, rapid reduction of the silver and chloroaurate ions is observed leading to the formation of highly stable silver and gold nanoparticles in solution. Transmission Electron Microscopy analysis of the silver and gold nanoparticles indicated that they ranged in size from 10 to 20 nm and 15 to 25 nm respectively. Ag and Au nanoparticles thus synthesized were then phase transferred into an organic solution using a cationic surfactant octadecylamine. Transmetallation reaction between hydrophobized silver nanoparticles and hydrophobized chloroaurate ions in chloroform resulted in the formation of gold nanoparticles.
Keywords: Biosynthesis; Nanomaterials; Phase transfer; Transmetallation

Gold nanotriangles biologically synthesized using tamarind leaf extract and potential application in vapor sensing - Ankamwar, Balaprasad; Chaudhary, M; Sastry, M (Synthesis and Reactivity in Inorganic Metal-Organic and Nano-Metal Chemistry, 2005)
The size and shape dependent electronic and chemical properties of metal nanoparticles has drawn the attention of chemists, physicists, biologists, and engineers who wish to use them for the development of new generation nanodevices. In this article, we report the synthesis of gold nanotriangles using tamarind leaf extract as the reducing agent. On treating aqueous chloroauric acid solution with tamarind leaf extract, rapid reduction of the chloroaurate ions is observed leading to the formation of flat and thin single crystalline gold nanotriangles. Atomic force microscopy analysis of the gold nanotriangles indicated that they ranged in thickness from 20 to 40 nm. These gold nanotriangles with unique and highly anisotropic planer shapes might find application in photonics, optoelectronics, and optical sensing. We investigated the effect of different organic solvent vapors like methanol, benzene and acetone on the conductivity of tamarind leaf extract reduced gold nanotriangles. I-V characteristics measurement of these nanotriangles was done in presence of these organic solvent vapors. The observed characteristics suggest the application of gold nanotriangles to future chemical sensors.
Keywords: Biosynthesis; gold nanotriangles; tamarind leaf; vapor sensing

Morphology and polymorphic phase changes of calcium carbonate micro/nanocrystals using fruit extracts - Ankamwar, Balaprasad (Journal of Nanoscience and Nanotechnology, 2011)
This study reveals the morphology and polymorphic phase changes of calcium carbonate crystals into a mixture of calcite and aragonite micro/nanocrystals of interesting morphology at room temperature by a simple reaction with fruit extracts of Tamarindus indica and Emblica officinalis respectively by mixing CaCO(3) solutions with their corresponding extracts. The control experiments were carried out to establish the plausible role of tartaric acid from Tamarindus indica and ascorbic acid from Emblica officinalis in this regard. The quantitative determination of CaCO(3) phases was done based on the use of intensities obtained from corresponding XRD spectrum. The molar %. of aragonite was found to be more in case of TA and AA rather than TI and EO respectively, however the calcite was observed to be the predominant phase in all four reactions. Interestingly, the TI changes the rhombohedral morphology of calcite to elongated rods, whereas EO induces a great polymorphic phase change.
Keywords: Aragonite; Calcite; Emblica officinalis; Morphology Changes; Polymorphic Changes; Tamarindus indica